A new flexible multicomponent model for the study of aerosol dynamics in the marine boundary layer - Karl, Matthias; Gross, Allan; Pirjola, Liisa; Leck, Caroline (Tellus B: Chemical and Physical Meteorology, 2016)
Peer reviewed